Widefield microwave imaging in alkali vapor cells with sub-100 μm resolution - Andrew Horsley; Guan-Xiang Du; Philipp Treutlein (New Journal of Physics, 2015)
We report on widefield microwave vector field imaging with sub- $100\;μ {\rm{m}}$ resolution using a microfabricated alkali vapor cell. The setup can additionally image dc magnetic fields, and can be configured to image microwave electric fields. Our camera-based widefield imaging system records 2D images with a 6 × 6 mm ^2 field of view at a rate of 10 Hz. It provides up to $50\;μ {\rm{m}}$ spatial resolution, and allows imaging of fields as close as $150\;μ {\rm{m}}$ above structures, through the use of thin external cell walls. This is crucial in allowing us to take practical advantage of the high spatial resolution, as feature sizes in near-fields are on the order of the distance from their source, and represent an order of magnitude improvement in surface-feature resolution compared to previous vapor cell experiments. We present microwave and dc magnetic field images above a selection of devices, demonstrating a microwave sensitivity of $1.4\;μ {\rm{T}}\;Hz^{-1/2}$ per $50× 50× 140\;μ {{\rm{m}}}^{3}$ voxel, at present limited by the speed of our camera system. Since we image 120 × 120 voxels in parallel, a single scanned sensor would require a sensitivity of at least $12\;nT\;Hz^{-1/2}$ to produce images with the same sensitivity. Our technique could prove transformative in the design, characterization, and debugging of microwave devices, as there are currently no satisfactory established microwave imaging techniques. Moreover, it could find applications in medical imaging.